2017
DOI: 10.4081/monaldi.2017.773
|View full text |Cite
|
Sign up to set email alerts
|

A study to estimate prevalence and risk factors of Obstructive Sleep Apnoea Syndrome in a semi-urban Indian population

Abstract: Obstructive Sleep Apnea Syndrome (OSAS) has been recognised as a major cause of morbidity and mortality in developing countries like India. There is still a paucity of Indian studies regarding the prevalence of OSAS. The current single centre prospective cross-sectional study was undertaken to know prevalence estimates for key symptoms and features that can indicate the presence of OSAS in an Indian population. A survey was conducted on subjects with age groups ≥25 years at King George's Medical University, Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…The prevalence of OSA in the Indian population is three-fold higher in men as compared to women (Reddy, 2009). According to a study by Singh et al, in North Indian population, it was found that 6.2% of the total populations were at high risk of OSAS whereas 33.5% of the obese population was at high-risk OSAS [1]. In our study, the prevalence of OSA was found to be 13.7% according to the STOP-Bang score which may be attributed to the higher BMI and presence of central obesity in this population ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of OSA in the Indian population is three-fold higher in men as compared to women (Reddy, 2009). According to a study by Singh et al, in North Indian population, it was found that 6.2% of the total populations were at high risk of OSAS whereas 33.5% of the obese population was at high-risk OSAS [1]. In our study, the prevalence of OSA was found to be 13.7% according to the STOP-Bang score which may be attributed to the higher BMI and presence of central obesity in this population ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSAS based on the Wisconsin cohort study performed in the USA involving middle-aged adults 30-60 years of age, is 2% in females and 4% in males (Young, 1993). According to a survey conducted on a semiurban Indian population, it was found that around 6.2% among total sample were diagnosed with high-risk OSAS and 33.5% of the obese population were at high risk of OSAS [1].…”
Section: Introductionmentioning
confidence: 99%
“…The main influencing mechanisms of OSAS ( 10 , 13 16 ), as a risk factor of CAD, are as follows: i) Hypoxemia in OSAS patients caused by repeated apnea can activate the chemical receptors and sympathetic nerve, resulting in vascular smooth muscle remodeling and hypertrophy, increasing oxygen consumption of heart and aggravating myocardial ischemia and hypoxia; ii) the platelet activity and aggregation capacity in OSAS patients are increased, leading to the occurrence of cardiovascular events; iii) the activity and content of tissue plasminogen activator inhibitor in OSAS patients are increased, inhibiting the fibrinolytic system in the body and leading to the hypercoagulable state, thrombosis and atherosclerosis development; iv) repeated apnea hypoxia activates the oxidative stress, which further leads to the lipid peroxidation, vascular endothelial cell injury and increased aggregation of inflammatory factors; v) nocturnal hypoxia may affect the activity of lipoprotein receptor, leading to the increased blood lipids and aggravating the development of atherosclerosis; and vi) accompanying factors: OSAS patients are mostly complicated by obesity, lipid metabolism disorders, hypertension, arrhythmia and other susceptibility factors of CAD. In order to reduce the incidence rate and improve the prognosis of CAD in OSAS patients, therefore, it is recommended to provide appropriate prevention and treatment for OSAS, as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…This was near to the result of an Indian study which found 62.4% of those with high risk were hypertensive, while only 5.3% of those with low risk had Discussion hypertension. 3 OSA was significantly higher in people who live in rural areas than those who live in urban areas, 50% and 22.4% respectively, (P = 0.024), but the small sample size of those in rural areas (only 14 persons) will reduce the importance of this difference. The socioeconomic status has a noticeable impact on OSAS, which was more prevalent among people with low and medium economic status than high socioeconomic class (27.0%, 28.8%, and 11.5% respectively), with a p-value less than 0.001.…”
Section: Characteristicmentioning
confidence: 91%